Managing COPD - Russell, Richard EK.; Ford, Paul A.; Barnes, Peter J.; Russell, Sarah; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
The book includes recommendations for COPD from published guidelines (eg, the GOLD, ATS, and NICE guidelines) and presents them in the context of relevant clinical treatment issues. This is an in-depth guide on the management of COPD, concentrating on the impact of COPD on a patient as well as how healthcare professionals can intervene and educate the patient at an early stage and thereby slow the onset of severe symptoms.
Introduction -- Epidemiology, risk factors and pathophysiology -- The clinical consultation -- Management strategies -- Palliative care in COPD -- The future of COPD.
Keywords: Medicine; Pneumology; Transplantation of organs, tissues, etc; Medicine & Public Health; Pneumology/Respiratory System; Pharmacotherapy; Transplant Surgery